Impact of socio-demographic factors on the decorative consumption of wristwatches among employees in Colombo - Karunanayake, C.; Gunaruwan, T.L. (University of Colombo, 2017)
The modern day person is involved in vicarious consumption patterns in order to showcase wealth, enhance prestige, and attract others’ attention through conspicuousness, exclusiveness, and emulation. We live in a society where consuming expensive goods is accepted as a mark of superior status. Yet, too little scholarly attention has been devoted to this obtrusive consumer desire in Sri Lanka and elsewhere in the world. In light of this, the purpose of this study is to explore what the authors denote as ‘decorative consumption’ and to examine the impact of socio-demographic factors on such consumption in terms of conspicuousness, snobbism, and conformism. This paper reports the outcomes of an exploratory survey conducted with 250 employees working within the Colombo city limits, to examine the concept of decorative consumption with regard to different ages, genders, sectors, religions, and income categories. The data gathered were analysed using SPSS (Version 20.0). The results highlighted that the socio-demographic factor ‘sector’ has a strong impact on the decorative consumption of wristwatches among employees working in Colombo as it is prone towards decorativeness in all three dimensions: conspicuousness, snobbism, and conformism. The results also revealed that ‘age’ and ‘religion’ could impact decorative consumption of wristwatches in the dimensions of conspicuousness and snobbism, whereas ‘monthly income’ is prone to influence decorative consumption in the dimensions of conspicuousness and conformism. The noteworthy outcomes that men appear to be more snobbish than women, and employees within the lowest income cohort are equally conspicuous and conformist as those in the richest income cohort, warrant further research to identify their causal factors.
Keywords: decorative consumption, wristwatches, socio-demographic factors, conspicuousness, snobbism, conformism